2012 IEEE International Conference on Embedded and Real-Time Computing Systems and Applications 2012
DOI: 10.1109/rtcsa.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Based Surface Recognition for Smartphones

Abstract: With various sensors in a smartphone, it is now possible to obtain information about a user and her surroundings, such as the location of a smartphone and the activity of the smartphone user, and the obtained context information is being used to provide new services to the users. In this paper, we propose VibePhone, which uses a built-in vibrator and accelerometer, for recognizing the type of surfaces contacted by a smartphone, enabling the sense of touch in smartphones. For humans and animals, the sense of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…A small but useful category of two places (soft and hard materials) can be distinguished in excess of 99% accuracy. We believe this is an excellent result considering the results of previous works [2,4]. In addition, we found that the vibration echoes change depending on the place within the same location.…”
Section: Preliminary Testsupporting
confidence: 85%
See 2 more Smart Citations
“…A small but useful category of two places (soft and hard materials) can be distinguished in excess of 99% accuracy. We believe this is an excellent result considering the results of previous works [2,4]. In addition, we found that the vibration echoes change depending on the place within the same location.…”
Section: Preliminary Testsupporting
confidence: 85%
“…This technique offers reliable and fast (or real-time) localization, but one disadvantage is that such hardware is still not supported in commercially available mobile devices. Given this background, some researchers have investigated the inertial sensors of mobile devices, such as their microphones or accelerometers [2,4]. Cho et al [2] introduced a surface recognition technique that used a built-in vibration motor and accelerometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On both works, there is no analysis connecting the device context and surface with falls detection. Moreover, [Cho et al 2012] shows the "VibePhone" solution, that focuses on the same concepts as the previous works. An 44º SEMISH -Seminário Integrado de Software e Hardware SVM (Support Vector Machine) is used to classify vibration data obtained from an accelerometer that varies according to the surface where a smartphone is placed.…”
Section: Related Workmentioning
confidence: 99%
“…Although imperative, knowing when a device/user is falling is not enough by itself without having surface dangerousness estimation. Another set of solutions tries to infer the surface characteristics where a device is placed [Darbar and Samanta 2015] [Cho et al 2012].…”
Section: Introductionmentioning
confidence: 99%